2011
DOI: 10.1007/s00018-011-0637-2
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles of basic helix-loop-helix transcription factors, Capsulin and Musculin, during craniofacial myogenesis of zebrafish

Abstract: Capsulin and Musculin are basic helix-loop-helix transcription factors, but their biophysiological roles in zebrafish cranial myogenesis are unclear. Expressions of endogenous capsulin transcripts are detected at the central- (~24-hpf) and at dorsal- and ventral-mesoderm cores (~30-72 hpf) of branchial arches. In contrast, musculin transcripts are expressed as a two-phase manner: early phase (20-22 hpf) expressions of musculin are detected at the head mesoderm, whereas late-phase (36-72 hpf) are detected at al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
(57 reference statements)
6
19
0
Order By: Relevance
“…During the next day, tcf21 expression refines to the cores of the pharyngeal arches, where it is surrounded by neural crest cells, and splits into dorsal and ventral clusters, which then divide further into smaller clusters (Figures 1G–1I). Later, mCherry from the tcf21:mCherry transgene labels most of the head muscles (Figures 1L, 1M, and 4A–4D) as suggested previously [2022, 26, 27]. However, mCherry also labels some of the dorsal and most of the ventral head vasculature, including part of the lateral dorsal aorta (LDA), the hypobranchial arteries (HAs), the pPAAs, and parts of the ventral aorta (VA) (Figures 1N, 1O, 4Q–4T, and 5A–5D).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…During the next day, tcf21 expression refines to the cores of the pharyngeal arches, where it is surrounded by neural crest cells, and splits into dorsal and ventral clusters, which then divide further into smaller clusters (Figures 1G–1I). Later, mCherry from the tcf21:mCherry transgene labels most of the head muscles (Figures 1L, 1M, and 4A–4D) as suggested previously [2022, 26, 27]. However, mCherry also labels some of the dorsal and most of the ventral head vasculature, including part of the lateral dorsal aorta (LDA), the hypobranchial arteries (HAs), the pPAAs, and parts of the ventral aorta (VA) (Figures 1N, 1O, 4Q–4T, and 5A–5D).…”
Section: Resultssupporting
confidence: 82%
“…Our and others’ genetic analyses show that the tcf21 + pharyngeal head muscle progenitors require Tcf21 activity for their specification [22, 26]. Similarly, we find that the tcf21 +/ nkx2.5 + vascular HA and pPAA progenitors require the joint activity of Tcf21 and Nkx2.5 for their specification, and previous studies have shown that Nkx2.5 is required for ventricular identity in the heart [4346].…”
Section: Discussionsupporting
confidence: 85%
“…embryos were washed with PBS and fixed in 4% paraformaldehyde. The procedures for whole-mount in situ hybridization, vascular alkaline phosphatase staining, and cryosections have been described previously (Pai and Chen 2010;Lee et al 2011), except that flk/kdrl (Lawson et al 2002) were used as probe.…”
Section: Methodsmentioning
confidence: 99%
“…4J). As a mesodermal marker, we monitored the expression of tcf21, which is also known as capsulin in zebrafish (Lee et al, 2011). In pax1 mutants, the expression of tcf21 marked the mesodermal cores of the first and second arches, but the posterior expression never exhibited the reiterative distribution of the arch cores (Fig.…”
Section: Reiterative Development Of the Third And Posterior Pouches Rmentioning
confidence: 99%